An emerging Africa in the age of globalisation - Mudida, Robert (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Since the turn of the century, Africa has been emerging economically, politically and socially, and striving to assert itself on the global stage. This book provides an interdisciplinary view of Africa's struggle to find its unique voice and contribute to the dialogue of international affairs. Highlighting both challenges and opportunities, the book explores the multi-faceted economic, political and social debates that surround Africa's emergence in a complex, increasingly globalised world. The author provides holistic, complementary and policy-oriented advice to African governments and policymakers on how to cope with new interrelated realities in an age of globalisation. This book will be of great interest to students, academics and researchers in the areas of political economy, international development, global governance, public policy and the international relations of African states. It will also appeal to African leaders, policymakers and governments who seek to increase the ability of their countries to cope with the challenges presented by a globalised world"--
Introducing an Emerging Africa in the Age of Globalisation -- New Frontiers in the Diplomacy of African States: Africa's Role in the Dialogue of Civilisations -- Africa's Ambitious Regional Integration Agenda: Challenges and Prospects of Africa's New Continental Free Trade Area -- Emerging Challenges of Human Rights Jurisprudence in Africa: The Case of the International Criminal Court and a New Clash of Civilisations -- The Changing Nature of Africa's Conflicts and Regional Security Architecture -- Africa's Challenges of Post-Conflict Peacebuilding -- The Political Economy of Africa's Development: Can Africa Overcome its Institutional Challenges to Development? -- Africa in the Age of the Sustainable Development Goals -- Africa's Health Sector Challenges and Policy Responses to the Global Covid-19 Pandemic -- Technological Innovation: Towards Sustaining Africa's Growth and Development Trajectory -- Conclusions: The Way Forward for an Emerging Africa in the Age of Globalisation.
Keywords: Globalization -- Africa -- 21st century; Economic development -- Africa -- International cooperation; Africa -- Foreign relations; POLITICAL SCIENCE / General